Pengalaman Siswa SMK dalam Mengikuti Layanan Konseling Individual di Sekolah - Sri Tika Sari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Individual counseling services are an important component of guidance and counseling programs that help students overcome various academic, social, personal, and career-related problems. Vocational high school students often face challenges that may affect their personal development and academic achievement. This study aimed to explore the experiences of vocational high school students in participating in individual counseling services and to identify the benefits they perceived after attending the sessions. The study employed a qualitative descriptive approach. The participants were students of SMK Negeri 2 Binjai who had previously received individual counseling services. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students attended individual counseling due to various issues, including learning difficulties, peer relationship problems, lack of self-confidence, academic stress, family problems, and uncertainty about their future careers. After participating in counseling sessions, students reported feeling relieved, calmer, and more comfortable. They also experienced improvements in learning motivation, self-confidence, emotional regulation, and social relationships. Therefore, individual counseling services contribute positively to students’ personal, social, and academic development.